Pengenalan Kosakata Bahasa Inggris bagi Siswa Sekolah Dasar sebagai Upaya Meningkatkan Kemampuan Vocabulary Dasar - Irmawaty Umar (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This community service program was conducted in response to the limited exposure of elementary school students to basic English vocabulary, particularly words related to objects in their immediate learning environment. Vocabulary mastery at an early age is essential to support the development of students’ foundational English skills, including listening and speaking. Therefore, this activity aimed to introduce and improve students’ English vocabulary through the topic “Things in the Classroom.”. The program was implemented at SDN 91 Kota Gorontalo and involved a group of elementary students as participants. The method applied interactive and student-centered teaching strategies, including the use of real classroom objects, visual aids, repetition drills, question-and-answer sessions, and educational games. These approaches were designed to create an enjoyable learning atmosphere and to encourage active participation. The activity was conducted in one instructional session consisting of vocabulary presentation, guided practice, and simple production activities. The results indicated that students showed high enthusiasm and active engagement throughout the session. Most participants were able to recognize, pronounce, and correctly mention classroom-related vocabulary at the end of the activity. The use of contextual and game-based learning strategies helped students understand and retain the new vocabulary more effectively. This program implies that interactive and contextual vocabulary instruction is effective in supporting young learners’ English acquisition. It is recommended that similar community service programs be conducted continuously to strengthen students’ basic English competence and increase their confidence in using simple English vocabulary.